Food, Conservation, and Energy Act of 2008: Conservation Stewardship Program (CSP) - Hicks, Erin, author; Seidl, Andrew, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2008)
The Conservation Stewardship Program (CSP), formerly called The Conservation Security Program (CSP) is a voluntary program that provides financial and technical assistance to promote the conservation and improvement of soil, water, air, energy, plant and animal life, and other conservation purposes on tribal and private working lands. Working lands include cropland, grassland, prairie land, improved pasture, and rangeland, as well as forested land that is an incidental part of an agriculture operation. In the first sign-up, CSP was offered in 18 watersheds located in 22 states. In 2005, the program is available in all 50 states, the Caribbean, and the Pacific Basin. The program provides equitable access to benefits to all producers, regardless of size of operation, crops produced, or geographic location.
Conservation Stewardship Program (CSP)
October 2008 Agricultural and resource policy report, no. 5
October 2008.
Keywords: Conservation Security Program (U.S.); Conservation Stewardship Program (U.S.); Incentives in conservation of natural resources -- United States; Agricultural conservation -- United States; Ranching -- Environmental aspects -- United States; Agriculture -- Environmental aspects -- United States; Contracts, Agricultural -- United States; Natural resources -- Law and legislation -- United States; Agricultural laws and legislation -- United States; Agricultural subsidies -- Law and legislation -- United States